2017
DOI: 10.1093/mnras/stx1594
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-enhanced metal-poor stars in the SDSS–APOGEE data base

Abstract: We identify six new CEMP stars ([C/Fe]> +0.7 and [Fe/H]< −1.8) and another seven likely candidates within the APOGEE database following Data Release 12. These stars have chemical compositions typical of metal-poor halo stars, e.g., mean [α/Fe] = +0.24 ± 0.24, based on the ASPCAP pipeline results. A lack of heavy element spectral lines impedes further sub-classification of these CEMP stars, however, based on radial velocity scatter, we predict most are not CEMP-s stars which are typically found in binary system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 133 publications
(210 reference statements)
0
4
0
Order By: Relevance
“…The radial velocity uncertainties provided in DR2 are the result of the combination of multiple radial velocity measurements, and if stars vary in radial velocity over the course of the Gaia observations they will have higher radial velocity uncertainties than expected from the precision for stars of their magnitude and effective temperature. This approach is similar to what was done to investigate binarity in CEMP stars discovered in the APOGEE survey (Kielty et al 2017).…”
Section: Radial Velocity Outlook With Gaiamentioning
confidence: 86%
“…The radial velocity uncertainties provided in DR2 are the result of the combination of multiple radial velocity measurements, and if stars vary in radial velocity over the course of the Gaia observations they will have higher radial velocity uncertainties than expected from the precision for stars of their magnitude and effective temperature. This approach is similar to what was done to investigate binarity in CEMP stars discovered in the APOGEE survey (Kielty et al 2017).…”
Section: Radial Velocity Outlook With Gaiamentioning
confidence: 86%
“…Stars in the nearby dwarf galaxies typically have lower abundances of αand odd-Z elements, attributed to their slower star formation histories and/or fewer number of high mass stars overall (Venn et al 2004;Tolstoy et al 2009;Nissen & Schuster 2010;McWilliam et al 2013;Frebel & Norris 2015;Hayes et al 2018), while significant variations in heavy r-process elements in some dwarf galaxies, and globular clusters, are discussed in terms of contributions from individual compact binary merger events, like GW170817 (e.g., Roederer 2011;Roederer et al 2018a;Ji et al 2016Ji et al , 2019. In addition, about a third of the [Fe/H] < −2.5 stars 1 in the Galactic halo show very high enhancements in carbon (the carbon-enhanced metal-poor stars, "CEMP"; Yong et al 2013;Aguado et al 2019a also see Kielty et al 2017;Mardini et al 2019), discussed as a signature of the earliest chemical enrichment in the Universe. However, at least one ultra metal-poor star is not carbonenhanced (SDSS J102915+172927, Caffau et al 2012), and the known metal-poor stars in the Galactic bulge do not show carbon-enhancements (Howes et al 2016;Lamb et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that metal-poor stars may show high carbon-to-iron ratios, and thus classified as carbon-enhanced metal-poor stars (Beers & Christlieb 2005;Aoki et al 2007;Hansen et al 2016a;Placco et al 2016;Kielty et al 2017;Roriz et al 2017;Cruz et al 2018;Caffau et al 2018). Furthermore, CEMP stars can be divided into four sub-classes, according to their neutron-capture elements nature.…”
Section: Introductionmentioning
confidence: 99%